Respuesta :
okay so basically i like to switch it around, you dont have to though.
1 Simplify 6x+4x-66x+4x−6 to 10x-610x−6
10x-6=24+9x1
2 Add 66 to both sides
10x=24+9x+610x=24+9x+6
3: Simplify 24+9x+624+9x+6 to 9x+309x+30
10x=9x+3010x=9x+30
4 Subtract 9x9x from both sides
10x-9x=3010x−9x=30
5 Simplify 10x-9x10x−9x to xx
x=30
Answer:
x = 30 it has only one solution equation is neither .
Step-by-step explanation:
Given : 6x + 4x - 6 = 24 + 9x .
To find: Solve the equation .
Solution: we have given that
6x + 4x - 6 = 24 + 9x .
Combine like term
10x - 6 = 24 + 9x
On subtracting both side by 9x
10x -9x -6 = 24 + 9x -9x
x -6 = 24
On addition both side by 6
x - 6 + 6 = 24 + 6
so , x = 30
Therefore , x = 30 it has only one solution equation is neither .